DETERMINAN MINAT INVESTASI MAHASISWA AKUNTANSI UNIVERSITAS SAMUDRA PADA PASAR MODAL - Reza Juliansyah; Azhar, Iqlima; Ainul Yusna Harahap (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
on the Investment Interest of Accounting students at the Faculty of Economics and Business, Universitas Samudra. Using a quantitative method, data were collected through questionnaires measured by a Likert scale. The population consisted of 213 Accounting students, and purposive sampling with Slovin’s formula was used to select a sample of 139 respondents. Multiple linear regression analysis was conducted with SPSS software. The results indicate that both investment knowledge and investment motivation have positive and significant effects on investment interest, both individually and simultaneously. However, this study is limited by its narrow variable scope, lack of differentiation based on respondents’ investment experience, and limited exploration of the campus environment’s role. Therefore, future research is recommended to include additional variables, distinguish respondents by investment experience, and further investigate the influence of the learning environment on investment interest.